Mechanisms underlying the formation of the amygdalar fear memory trace: A computational perspective. (13th May 2016) - Feng, F.; Samarth, P.; Paré, D.; Nair, S.S.
Graphical abstract: Highlights: Mechanisms implementing cellular competition during fear memory formation are unknown. A biophysical network model provided insights into the intrinsic and synaptic mechanisms. Only PNs with access to input about the conditioned stimulus participated in the competition. PNs receiving the least disynaptic inhibition and having NE and DA receptors won the competition. The overall level of inhibition also controlled the size of the fear memory trace. Abstract: Recent experimental and modeling studies on the lateral amygdala (LA) have implicated intrinsic excitability and competitive synaptic interactions among principal neurons (PNs) in the formation of auditory fear memories. The present modeling studies, conducted over an expanded range of intrinsic excitability in the network, revealed that only excitable PNs that received tone inputs participate in the competition. Strikingly, the number of model PNs integrated into the fear memory trace remained constant despite the much larger range considered, and model runs highlighted several conditioning-induced tone responsive characteristics of the various PN populations. Furthermore, these studies showed that although excitation was important, disynaptic inhibition among PNs is the dominant mechanism that keeps the number of plastic PNs stable despite large variations in the network's excitability. Finally, we found that the overall level of inhibition in the model network determines the number of projection cells integrated into the fear memory trace.